The semi-synthetic kaurane ent-16 alpha-methoxykauran-19-oic acid induces vascular relaxation and hypotension in rats - Hipolito, Ulisses V.; Rocha, Juliana T.; Palazzin, Nathalia B.; Rodrigues, Gerson Jhonatan [UNESP]; Crestani, Carlos Cesar [UNESP]; Correa, Fernando M.; Bonaventura, Daniella; Ambrosio, Sergio R.; Bendhack, Lusiane M.; Resstel, Leonardo B.; Tirapelli, Carlos R. (Elsevier B.V., 2011)
The present work investigates the mechanisms involved in the vasorelaxant effect of ent-16 alpha-methoxykauran-19-oic acid (KA-OCH(3)), a semi-synthetic derivative obtained from the kaurane-type diterpene ent-kaur-16-en-19-oic acid (kaurenoic acid). Vascular reactivity experiments were performed in aortic rings isolated from male Wistar rats using standard muscle bath procedures. The cytosolic calcium concentration ([Ca(2+)]c) was measured by confocal microscopy using the fluorescent probe Fluo-3 AM. Blood pressure measurements were performed in conscious rats. KA-OCH(3) (10,50 and 100 mu mol/l) inhibited phenylephrine-induced contraction in either endothelium-intact or endothelium-denuded rat aortic rings. KA-OCH(3) also reduced CaCl(2)-induced contraction in a Ca(2+)-free solution containing KCl (30 mmol/l) or phenylephrine (0.1 mu mol/l). KA-OCH(3) (0.1-300 mu mol/l) concentration-dependently relaxed endothelium-intact and endothelium-denuded aortas pre-contracted with either phenylephrine or KCl, to a greater extent than kaurenoic acid. Moreover, a Ca(2+) mobilisation study showed that KA-OCH(3) (100 mu mol/l) inhibited the increase in Ca(2+) concentration in smooth muscle and endothelial cells induced by phenylephrine or KCl. Pre-incubation of intact or denuded aortic rings with N(G)-nitro-L-arginine methyl ester (L-NAME, 100 mu mol/l), 7-nitroindazole (100 mu mol/l), wortmannin (0.5 mu mol/l) and 1H-[1,2,4]Oxadiazolo[4,3-a]quinoxalin-1-one (ODQ 1 mu mol/l) produced a rightward displacement of the KA-OCH(3) concentration-response curve. Intravenous administration of KA-OCH(3) (1-10 mg/kg) reduced mean arterial blood pressure in normotensive rats. Collectively, our results show that KA-OCH(3) induces vascular relaxation and hypotension. The mechanisms underlying the cardiovascular actions of KA-OCH(3) involve blockade of Ca(2+) influx and activation of the NO-cGMP pathway. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: ent-16 alpha-methoxykauran-19-oic acid; Relaxation; Rat aorta; Diterpene; Ca(2+)